2012
DOI: 10.1111/j.1755-3768.2012.t123.x
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography: a window into the brain of schizophrenic patients

Abstract: Purpose Our study aims to assess peripapillary retinal nerve fiber layer (RNFL) thickness, macular thickness and volume, and optic nerve head (ONH) measurements in patients affected by schizophrenia Methods 30 schizophrenic patients (mean age 44.5 +/‐ 10.9 years) were enrolled. They were compared with 30 age‐matched controls. In all subjects, peripapillary RNFL thickness, ONH measurements, macular thickness and volume were measured by optical coherence tomography (OCT). The eye studied was the right eye Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 0 publications
2
22
1
2
Order By: Relevance
“…They found that these measurements were reduced in schizophrenia patients, suggesting that SD-OCT could be a useful tool for schizophrenia diagnosis and monitoring [26••]. These results agree with the study by Cabezon et al [30] who showed significant average and superior peripapillary RNFL thinning in 30 schizophrenia patients. Ascaso et al [31] found a significant difference between RNFL thickness in schizophrenia patients compared to healthy subjects in the nasal quadrant.…”
Section: Dopamine and Glutamine Rolesupporting
confidence: 79%
“…They found that these measurements were reduced in schizophrenia patients, suggesting that SD-OCT could be a useful tool for schizophrenia diagnosis and monitoring [26••]. These results agree with the study by Cabezon et al [30] who showed significant average and superior peripapillary RNFL thinning in 30 schizophrenia patients. Ascaso et al [31] found a significant difference between RNFL thickness in schizophrenia patients compared to healthy subjects in the nasal quadrant.…”
Section: Dopamine and Glutamine Rolesupporting
confidence: 79%
“…38 Another study by Chu et al 39 showed that there was no difference in the RNFL thickness and macula volume in 38 schizophrenic patients compared to healthy controls. This finding was disagreed with by Cabezon et al, 40 who showed significant overall and superior peripapillary RNFL thinning in his 30 schizophrenic patients. Chu et al 39 suggested that unmyelinated axons in schizophrenic patients remained unaffected by the disease process.…”
Section: Discussioncontrasting
confidence: 62%
“…However, it must be pointed out that the study of Chu et al 39 used the Stratus OCT with lower resolution that may be inadequate to detect the subtle abnormalities. On the other hand, Cabezon et al 40 found an overall peripapillary RNFL thinning in the schizophrenic patients without any statistically significant thinning in the macula region. This contradicted our findings of significant overall peripapillary RNFL thinning with corresponding macula fiber thinning, supporting a generalized structural RNFL loss in schizophrenic patients.…”
Section: Discussionmentioning
confidence: 90%
“…123 However, studies containing similar numbers of patients and controls have reported no significant correlation between RNFL thickness or macular thickness with duration of illness. 74,79 The Ascaso study (n = 60) found no correlation between duration and retinal abnormalities; however, the finding of macular thinning in patients with nonrecent illness episodes suggests that changes in retinal structures may be conditional as opposed to progressive. 75 Similarly, Chu and colleagues reported no significant retinal changes between early stage schizophrenia patients and schizoaffective disorder to age and gender-matched controls.…”
Section: Severity and Duration Of Schizophreniamentioning
confidence: 98%